Book Review: Buddhist Festivals and Traditions — English Translation - Aomkaewvarasmi, Phramaha Kantabadh (Mahachula Academic Journal, 2026)
Abstract This review critically examines Buddhist Festivals and Traditions, the English translation of the Thai textbook for course 000 238 at Mahachulalongkornrajavidyalaya University. It evaluates the volume in terms of Buddhist content, pedagogical organization, accuracy and consistency of English usage, transliteration of Pali and Thai terms, scriptural and scholarly documentation, and suitability for international students and general readers. The study employs critical content analysis, reading all ten English chapters in relation to the bibliographical and front-matter information of the Thai edition. Five evaluative criteria are applied: clarity of purpose, structural coherence, academic accuracy, translation quality, and practical usefulness. The review finds three major strengths. First, the book offers an extensive and systematic account of Buddhist festivals, traditions, and rituals, moving from foundational concepts and historical developments to Thai social influence, regional diversity, ethical value, royal and state ceremonies, and the practical work of a religious master of ceremonies. Second, the newly added overview chapter gives readers from different cultural backgrounds an effective conceptual map of the volume. Third, the book has considerable applied value because it connects Buddhist teachings with family and community life, culture, education, economy, the environment, and the actual performance of ceremonies. These strengths make it a useful teaching text and an important medium for the international dissemination of Thai Buddhist knowledge. Nevertheless, several revisions are recommended. The terms festival, tradition, ritual, and ceremony are not always used consistently; titles of scriptures and abbreviations of the Tipitaka follow multiple systems; footnotes and bibliographical entries require a unified style; some online references are unstable or academically weak; and several chapters are more descriptive than analytical. The original English title, Buddhist Festival and Traditions, should also be corrected to Buddhist Festivals and Traditions. A book-wide glossary, a systematic verification of scriptural citations against explicitly identified editions, standardized references, and more comparative discussion of contemporary multicultural society would substantially improve the work. With these revisions, the volume has strong potential to become a standard English-language textbook of the university and a valuable resource for presenting Thai Buddhist culture to an international readership. Keywords: Buddhist festivals; rituals; Thai traditions; English translation; religious ceremonies; Buddhist culture